CRISPR: A Useful Genetic Feature to Follow Vaginal Carriage of Group B Streptococcus - Beauruelle, Clémence; Pastuszka, Adeline; Horvath, Philippe; Perrotin, Franck; Mereghetti, Laurent; Lanotte, Philippe (Frontiers in Microbiology, 2017)
CRISPR (clustered regularly interspaced short palindromic repeats) and Cas (CRISPR-associated proteins) play a critical role in adaptive immunity against mobile genetic elements, especially phages, through their ability to acquire novel spacer sequences. Polarized spacer acquisition results in spacer polymorphism and temporal organization of CRISPR loci, making them attractive epidemiological markers. Group B Streptococcus (GBS), a genital commensal for 10 to 30% of healthy women and a major neonatal pathogen, possesses a ubiquitous and functional CRISPR1 locus. Our aim was to assess the CRISPR1 locus as an epidemiological marker to follow vaginal carriage of GBS in women. This study also allowed us to observe the evolution of the CRISPR1 locus in response to probable phage infection occurring in vivo. We followed carriage of GBS among 100 women over an eleven-year period, with a median duration of approximately two years. The CRISPR1 locus was highly conserved over time. The isolates that show the same CRISPR1 genotype were collected from 83% of women. There was an agreement between CRISPR genotyping and other typing methods (MLVA [MultiLocus Variable number of tandem repeat Analysis] and MLST [MultiLocus Sequence Typing]) for 94% of the cases. The CRISPR1 locus of the isolates from 18 women showed modifications, four of which acquired polarized spacer, highlighting the in vivo functionality of the system. The novel spacer of one isolate had sequence similarity with phage, suggesting that phage infection occurred during carriage. These findings improve our understanding of CRISPR-Cas evolution in GBS and provide a glimpse of host-phage dynamics in vivo.